The incubus phenomenon: Prevalence, frequency and risk factors in psychiatric inpatients and university undergraduates - Molendijk, Marc L.; Bouachmir, Ouarda; Montagne, Harriët; Bouwman, Laura; Blom, Jan Dirk (Frontiers in Psychiatry, 2022)
Background: The incubus phenomenon is a paroxysmal sleep-related disorder characterised by the visuotactile sensation of a person or entity exerting pressure on one’s thorax during episodes of sleep paralysis and (apparent) wakefulness. This terrifying phenomenon is relatively unknown even though a previous meta-analysis indicated a lifetime prevalence of .11 for individuals in the general population and of .41 for selected at-risk groups, including people diagnosed with schizophrenia and students. Since the studies reviewed did not always make a strict distinction between the incubus phenomenon and isolated sleep paralysis, we carried out a cross-sectional study in a contemporary patient and a student sample to attain current, more detailed data on the incubus phenomenon. Methods: In a cross-sectional design, we used the Waterloo Unusual Sleep Experience Questionnaire (WUSEQ) to screen patients with severe psychiatric disorders and university undergraduates to establish and compare prevalence rates, frequencies of occurrence, and risk factors for the incubus phenomenon. Results: Having interviewed 749 people, comprising 606 students and 143 patients with a schizophrenia spectrum or related disorder who had been acutely admitted to a secluded nursing ward, we computed a reported lifetime prevalence of .12 and .09, respectively, which rates were not statistically different. In both groups, the phenomenon was more common in people with a non-Western European background. Risk factors noted for the students were the use of psychotropic medication and the lifetime presence of an anxiety disorder, eating disorder, or sleeping disorder. We found no associations with age or gender in either group. Conclusions: The .09 and .12 lifetime prevalence rates we recorded for the incubus phenomenon in students and psychiatric inpatients is substantially lower than the .41 found in an earlier meta-analysis. We tentatively attribute this difference to an overgeneralisation in previous studies but also discuss alternative explanations. The elevated prevalence among non-Western European participants may well be due to the fact that the topic continues to be part of the cultural and religious heritage of many non-Western countries.